Deep-sea living (stained) benthic foraminifera from the continental slope and São Paulo Plateau, Santos Basin (SW Atlantic): ecological insights - Beatriz D. Araújo; Cintia Yamashita; Ana C. A. Santarosa; Amanda V. Rocha; Thaisa M. Vicente; Rafaela N. M. Mendes; Camila C. Passos; Maria Virginia Alves Martins; Silvia Helena M. Sousa (Ocean and Coastal Research)
This study aimed to characterize the spatial distribution and composition of living Benthic Foraminifera (BF) and to comprehend how environmental conditions (e.g., organic matter) can affect communities of these protozoa in the northern and southern sectors of the Santos Basin (SB), in the continental slope and São Paulo Plateau. In this context, 23 stations (65 samples including replicates at each station) were collected between 400 and 2,400 m water depth. Multivariate analyses revealed that the ecological structure of the community changes mainly along the bathymetric gradients. Stations located between 400 and 700 m, both in northern and southern sectors, are characterized by the presence of indicator species of high intensity of currents, such as Globocassidulina subglobosa and Trifarina bradyi. These stations are also mainly marked by the occurrence of Epistominella exigua, a phytodetritivore species. The stations at 1,000 and 1,300 m depth, in both sectors, are characterized by high accumulation of organic matter in the sediments, which favors the development of agglutinated foraminifera species, such as those of the genus Reophax. Finally, the lower slope and the São Paulo Plateau, in both sectors, are oligotrophic regions, with pulses of labile organic carbon, probably low current velocities and the presence of Alabaminella weddellensis. The quantity and quality of food, which are closely related to hydro-sedimentary dynamics and bentho-pelagic coupling in the slope and São Paulo Plateau, are the main factors that influence the distribution of living BF assemblages in the SB.